Design and Fabrication of Epicyclic Internal Gear Pump - Pawar, Omkar S.; Suryavanshi, Sushil C.; Khamkar, Suyog B.; Shinde, Paresh D.; Raut, A. S. (Journal of Advance Research in Mechanical and Civil Engineering (ISSN: 2208-2379), 2015)
This paper gives outlines Epicyclic internal gear pump where one sun gear is meshed with three planet gears to achieve variable discharge rate as per requirement. This paper describes techniques for the design, construction, and testing of a Epicyclic internal gear pump. In many applications it is required to drive the actuators hydraulic cylinder or hydraulic motors at variable speed. This is only possible by variable discharge from a variable displacement pump (this pump has very high cost approx Rs.90000/-) so it is not possible to use it. One method employed is to use a pump of higher discharge capacity. But higher capacity means higher cost and higher power consumption. Hence there is need of special pump system at low cost so that the requirement of variable discharge is met easily without much cost and set up.